(untitled) (Revista de Crítica Literaria Latinoamericana, 2013)
This article discusses the relationship between the narrative work of José María Arguedas and contemporary Peruvian theatricality. First, it proposes the incorporation of the concept of theatricality to interpret the performative elements in the work of Arguedas, and to understand how this narrative has served as a source for theatre productions and performances. The article also presents how such theatricality in Arguedas is nowadays discussed as the connection between cultural memory and artistic practices. Then, it reviews the ciclos arguedianos in the New Peruvian Theater, presenting three very recent cases (Cuatrotablas, Waytay, Comunidad de Recordantes de Villa El Salvador) which show a dialogue between social theatricality and memory